Subthalamic deep brain stimulation and trunk posture in Parkinson's disease. (29th December 2017) - Artusi, C. A.; Zibetti, M.; Romagnolo, A.; Rizzone, M. G.; Merola, A.; Lopiano, L.
Abstract : Objectives: We sought to assess the efficacy of subthalamic nucleus deep brain stimulation (STN‐DBS) in Parkinson's disease (PD)‐associated trunk posture abnormalities retrospectively analyzing data from 101 patients reporting mild‐to‐severe trunk posture abnormalities of a cohort of 216 PD patients treated with STN‐DBS at our center. Methods: Abnormal trunk posture was rated on a scale of 0 (normal) to 4 (marked flexion with an extreme abnormality of posture) as per the grading score reported in the Unified Parkinson's Disease Rating Scale. The independent effect of STN‐DBS on trunk posture was assessed comparing Medication‐Off (presurgery) vs Stimulation‐On/Medication‐Off (post‐surgery). The combined effect of STN‐DBS plus levodopa was evaluated comparing Medication‐On (presurgery) vs Stimulation‐On/Medication‐On (post‐surgery). Analyses were conducted considering both the entire cohort of patients and the subgroup with camptocormia (CMC) and Pisa syndrome (PS). Results: The independent effect of STN‐DBS resulted in a 41.4% improvement in abnormal trunk posture severity ( P < .001), with 78.2% of patients (n = 79) reporting an improvement of at least 1 point. The combined effect of STN‐DBS and levodopa resulted in a 30.9% improvement ( P = .061), with 54.5% of patients (n = 55) reporting an improvement of at least 1 point. The subanalysis of patients with CMC (n = 23) and PS (n = 5) showed a 42.7% improvement in abnormal posture severity when considering the independent effect of STN‐DBS ( P < .001) and 30.5% when considering the combined effect of STN‐DBS and levodopa ( P < .001). Conclusions: STN‐DBS may have the potential for improving posture in patients with advanced PD.